ANALISIS METHOD DALAM DEBAT “KENAKALAN ANAK SD” PADA PEMBELAJARAN KETERAMPILAN BERBAHASA - Anita Dewi Kurniasari; Atiqa Sabardila (Universitas Muhammadiyah Tapanuli Selatan, 2020)
his article attempts to analyze the graduate student debate method in encouraging skills learning. The subject was a second year MPBI students at the Muhammadiyah University of Surakarta. Focuses on Analysis Methods of postgraduate student debates in learning skills. Data translated from the sentence transcript of the debate